Transurethral Resection of a Large Urinary Bladder Leiomyoma: A Rare Case Report - Gok, Alper (Urology Journal, 2017)
Bladder leiomyoma constitutes less than 0.5% of all bladder tumors. Until now, there have been about 250 case reports of bladder leiomyoma. We present a case of large bladder leiomyoma, that was treated successfully with transurethral resection. The patient presented to our clinic with both obstructive and irritative urinary complaints. Cystoscopy showed a mass lesion completely obstructing the bladder neck at the junction of right lateral wall and floor, which did not extend to ureteral orifices. A transurethral resection was performed at the same session of cystoscopy. At the postoperative 3rd month control visit, the patient’s obstructive symptoms were completely healed but her irritative symptoms continued. A repeat cystoscopy revealed residual tumoral tissue remaining at the floor of the previous surgical area. Transurethral resection was performed, and these tissues were completely resected. At the control visit that was 3 months after the second transurethral resection procedure, the patient was free from any urinary complaints. In conclusion, large bladder leiomyomas can be treated successfully with endoscopic approaches.